Systemic to pulmonary collateral blood flow influences early outcomes following the total cavopulmonary connection. Issue 12 (23rd May 2012) - Odenwald, Tobias; Quail, Michael A; Giardini, Alessandro; Khambadkone, Sachin; Hughes, Marina; Tann, Oliver; Hsia, Tain-Yen; Muthurangu, Vivek; Taylor, Andrew M
Abstract : Background: Systemic to pulmonary collaterals (SPCs) represent an additional and unpredictable source of pulmonary blood flow in patients with single ventricle physiology following bidirectional superior cavopulmonary connection (BCPC). Understanding their influence on patient outcomes has been hampered by uncertainty about the optimal method of quantifying SPC flow. Objective: To quantify SPC flow by cardiac magnetic resonance (CMR) prior to total cavopulmonary connection (TCPC) in order to identify preoperative risk factors and determine influence on postoperative outcomes. Design: Single centre prospective cohort study. Setting: Tertiary referral centre. Patients: 65 patients with single ventricle physiology undergoing CMR for preoperative assessment of TCPC completion underwent quantification of SPC flow. Clinical outcomes of 41 patients in whom TCPC was completed were obtained. Main outcome measures: Early post-TCPC clinical outcomes associated with SPC flow were assessed, including postoperative chest drainage volume, postoperative chest drainage duration and length of intensive care and hospital stays. Additionally preoperative covariates associated with SPC flow were assessed including age at BCPC and CMR, SpO2 at BCPC and CMR, ventricle type, pulmonary artery (PA) cross-sectional area and PA pulsatility. Different methods of CMR SPC flow quantification were compared. Results: Higher SPC flow was associated with increased postoperative chest drain volume (r=0.51, p=0.001), chest drain duration (r=0.43, p=0.005), and intensive care unit (r=0.32, p=0.04) and log-transformed hospital stays (r=0.31, p=0.048). The effect of SPC flow on outcome was independent of fenestration, ventricle type and function. Preoperative covariates associated with SPC flow included age at BCPC (β=−0.34, p=0.008), SpO2 at time of CMR (β=0.34, p=0.004) and branch PA cross-sectional area (β=−0.26, p=0.036), model R 2 =0.34. Moreover, patients with pulsatile pulmonary blood flow had lower SPC flow than those without (0.8 vs 1.3 l/min/m 2 p=0.012). SPC flow calculated by the difference between pulmonary venous return and pulmonary artery flow (l/min/m 2 ) showed greatest association with preoperative covariates and strongest correlation with postoperative outcomes compared with other methods of quantification. Conclusions: CMR can provide an effective measurement of SPC flow prior to TCPC. Young age at BCPC, high preoperative oxygen saturation and smaller PAs are associated with increased SPC flow, which may promote increased postoperative pleural drainage and lengthen recovery.